Classification auditting scheme for privacy protection of outsourced EHR based on distributed storage - ZHANG Xiaoxu; CHEN Yuchen; HA Guanxiong; JIA Chunfu (Tongxin xuebao)
With the development of the electronic medical field, Electronic health record (EHR) are often outsourced to fog nodes for distributed storage to enhance reliability. EHR contains a large amount of private information, however, data outsourcing can create security risks, potentially compromising the integrity and privacy of EHR. In order to ensure the secure storage of EHR, an efficient distributed data integrity auditing scheme based on EHR classification was proposed. The scheme combined classification labels with Bloom filters to enhance auditing efficiency, Shamir’s secret sharing was used for distributed auditing, and attribute-based searchable encryption was employed to protect the privacy of EHR’ category information. Experimental results show that the proposed scheme has low communication and computation costs.